Re‐examination of the C6Li6 Structure: To Be, or not To Be Symmetric. Issue 38 (19th July 2013) - Moreno, Diego; Martínez‐Guajardo, Gerardo; Díaz‐Celaya, Andrés; Mercero, José M.; de Coss, Romeo; Perez‐Peralta, Nancy; Merino, Gabriel
Abstract The potential energy surface of C6Li6 was re‐examined and a new non‐symmetric global minimum was found. The new structure can be described as three C22− fragments strongly aggregated through lithium bridges. At high temperatures, fluxionality is perceived instead of dissociation. At 600 and 900 K, the BOMD simulations show that the lithium mobility is high, indicating that the cluster behaves in a liquid‐like manner (BOMD=Born–Oppenheimer molecular dynamics).